2008
DOI: 10.17305/bjbms.2006.3206
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Function Improvement in Patients Undergoing Regular Hemodialysis: Relation to Sex Differences

Abstract: Uremic lung is different entity then oedema present in cardiovascular diseases or in adult respiratory distress syndrome as well. This state is one of the possible complications in patients with chronic renal failure (CRF) receiving regular hemodialysis (HD). There are several studies suggesting that in these patients in 30-40% cases pulmonary hypertension was developed. It is known that patients with primary pulmonary hypertension have peripheral airway obstruction The data also showed that primary as well se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…In group 1, after haemodialysis, FEV1 value is highly improved (p<0.01), while in group 2 (with greater interdialysis gain) FEV1 is recovered, but without statistical significance (p>0.05). Results of other studies conducted on patients suffering from uraemia, show significant FEV1 recovery after haemodialysis, which is similar to our findings [7][8][9][10][11][12][13]. Positive effect of haemodialysis on FEV1 is more expressed in group 1 (patients with interdialysis liquid gain < 5%) than in group 2 (patients with interdialysis liquid gain > 5%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In group 1, after haemodialysis, FEV1 value is highly improved (p<0.01), while in group 2 (with greater interdialysis gain) FEV1 is recovered, but without statistical significance (p>0.05). Results of other studies conducted on patients suffering from uraemia, show significant FEV1 recovery after haemodialysis, which is similar to our findings [7][8][9][10][11][12][13]. Positive effect of haemodialysis on FEV1 is more expressed in group 1 (patients with interdialysis liquid gain < 5%) than in group 2 (patients with interdialysis liquid gain > 5%).…”
Section: Discussionsupporting
confidence: 91%
“…FEV1 before haemodialysis in patients with lower interdialysis intake (group 1) are significantly lower (p<0.05) compared to the stated values in patients with greater interdialysis intake (group 2). The reason for these findings might be found in difference in heamodialysis duration, sex, age, and some other antropometric parameters (height and weight) that influence vital capacity values [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results tie in with several studies showing a reduction in respiratory muscle strength and changes in lung function of patients on HD compared with the predicted values for age or healthy subjects (22)(23)(24) . Other studies have evaluated the acute effects of HD on strength and lung function and showed that the weight gained between dialysis sessions has deleterious effects on respiratory function (25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of uremia are also present in the lungs. The ventilatory function disorder in this group of patients is mainly presented as an obstructive pulmonary disease [1][2][3]. Apart from these findings, a number of medical journals provides data stating the existence of a vasoactive molecule imbalance in uremic patients, primarily endothelin-1 (ET-1) [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%